FAKTOR-FAKTOR YANG MEMPENGARUHI KEBIJAKAN DIVIDEN PERUSAHAAN MANUFAKTUR DI BEI - Neswari, Prajna Paramita Ardana; Priyadi, Maswar Patuh (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
ABSTRACTThis research is aimed to test: (1) the influence of free cash flow to the dividend policy; (2) the influence ofprofitability to the dividend policy; (3) the influence of investment opportunity set to the dividend policy; (4) theinfluence of debt policy to the dividend policy; (5) the influence of managerial ownership to the dividend policy.In this research, free cash flow has been measured by using Ross et al formula, profitability has been measured byusing return on asset, investment opportunity set has been measured by using Ratio Capital Expenditure toBook Value of Asset, the debt policy has been measured by using debt to asset ratio, the managerial ownershiphas been measured by using capital stock of directors and commissioners which are divided by the numbers ofoutstanding stocks. The population is all manufacturing companies which are listed in Indonesia Stock exchangein 2010-2015 periods. In this research, the sample collection has been determinedand carried out by usingpurposive sampling, and 156 companies have been selected as samples. This research has been conducted byusing multiple linear regressions analysis technique. The results of this research are: (1) free cash flow does nothave any influence to the dividend policy; (2) profitability has influence to the dividend policy; (3) investmentopportunity set has influence to the dividend policy; (4) debt policy does not have any influence to the dividendpolicy; (5) managerial ownership has an influence to the dividend policyKeywords: Free cash flow, profitability, investment opportunity set, debt policy, managerial ownership,and dividend policy.